PENERAPAN METODE SOSIODRAMA DALAM MENINGKATKAN MINAT BELAJAR, KEAKTIFAN, DAN HASIL BELAJAR MATA PELAJARAN PAI, KELAS 10, TEKNIK PERMESINAN, SMKN I MLARAK, PONOROGO - Ratna Untari (AL-ASASIYYA: Journal Of Basic Education, 2018)
Ideally, in Learning needs to be emphasized learning interests and activeness of students to get the desired learning outcomes. As a learning centre, students must be more active in activities to build an understanding, skills, and attitude, because the nature of learning is an active process in which students use their minds to build understanding. In reality, problems arise in the learning process such as: students pay less attention to lessons, go in and out of class without permission, chat with other friends, and get bored with the monotonous teacher teaching method. For this reason, improving the quality of education must be carried out, one of which is by applying methods that can enhance, interest in learning, activeness and student learning outcomes. This study aims to explain the increasing interest in learning, activeness, and learning outcomes of students with the method of sociodrama in class 10, Machining Engineering, SMKN 01 Mlarak, Ponorogo, East Java. This type of research is classroom action research that is presented in two cycles. Each cycle consists of 4 stages, namely: planning, actuating, observation, and reflecting. Based on data analysis, it was found that the sociodrama method could improve students' learning interest, student activity in learning, and student learning outcomes. This can be seen from the increase from cycle I to cycle II.